The Psychometric Properties of the Grief Recovery Scale (A Field Study in the City of Ouargla, Algeria ( - Salma, Maache; Keltoum, Guir; Chahrazed, Nouar; Nardjess, Zekri (Journal of Ecohumanism, 2025)
The present study aimed to identify the psychometric properties of the Grief Recovery Scale and to verify its validity and reliability. To achieve this objective, the study was conducted on a sample of (80) individuals who had lost a family member, selected randomly.The results of the study showed that the Grief Recovery Scale has high levels of validity and reliability (criterion validity, internal consistency reliability, Cronbach’s alpha, and split-half reliability), which indicates that its psychometric properties are consistent with those of a good test and that it can be used in subsequent studies.